The strategy of introducing a new serviced residence to the Prague accommodation market - Utkina, Alina; Petrů, Zdenka, 1953-; Kovařík, Zdeněk; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2022)
The aim of the thesis is to present a marketing strategy for a new serviced residence during the introduction period in the Prague market of accommodation facilities. The first part defines the theoretical basis for marketing in the services and the typology of tourist accommodation. The second part presents the market analysis including the market analysis of serviced apartments in Prague, PEST and SWOT analyses, and competitive analysis. In the final part, a marketing strategy is proposed. Based on the analyses performed, the new serviced residence is positioned in the market as an upscale accommodation with a wide range of services targeting leisure travelers, including families, business clients, and digital nomads. Thanks to the small number of competitors in the location and an innovative product, the residence can apply a rapid-skimming pricing strategy during the introduction stage.
Vedoucí práce: Zdenka Petrů
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: cestovní ruch [obor dipl. práce]; diplomové práce; master's theses